(untitled) (LACCEI, 2024)
Herein, it examines the current situation of the order-picking process in the low-turnover area of a cosmetics company. The existence of long travel times for the search and selection of products is verified. The primary purpose of this study is to design and computationally validate a multi-criteria model to increase the productivity of the order-picking process in the low-turnover area. The case study is based on products stored for a commercial cycle (c.a. 17 days). The spatial location and the selection times of 20 products were analyzed by mathematical criteria. As a result, new spatial distribution and lower travel times within the picking process are reported. Subsequently, a computational validation of this multi-criteria model was performed by Arena simulation software. All possible variants that could represent the order-picking process in the low turnover were analyzed and compared, concluding that productivity increased by 19% with productivity increased by 19% with this multi-criteria model without generating additional costs for the company.